In Vitro Comparison of Two Widely Used Surgical Sealants for Treating Alveolar Air Leak - Zhang, Ruoyu; Bures, Maximilian; Höffler, Klaus; Jonigk, Danny; Haverich, Axel; Krueger, Marcus (The Thoracic and Cardiovascular Surgeon, 2014)
Background Controversies surrounding the efficacy of sealants against alveolar air leak (AAL) are abundant in the literature. We sought to test the widely used sealants, TachoSil (Takeda Pharmaceutical Company Limited, Osaka, Japan) and BioGlue (CryoLife Europa Ltd., Surrey, United Kingdom) in an in vitro model.Materials and Methods After creation of a focal superficial defect (40 × 25 mm) in swine lungs (n = 40), AAL was assessed with increasing inspired tidal volume (TVi). Upon sealant application in a randomized order, AAL was assessed in the same way until sealant burst.Results At TVi = 400, 500, 600, and 700 mL, BioGlue achieved sealing in 19, 19, 16, and 14 tests, while TachoSil sealed in 19, 14, 4, and no test, respectively. The maximally tolerated pressure of BioGlue was higher than TachoSil (40.3 ± 3.0 vs. 36.0 ± 4.9 cm H2O, p = 0.003). Cohesive and adhesive failures were found in 10 and 1 tests of BioGlue, respectively, while all burst failures of TachoSil were adhesive. Concerning elasticity, TachoSil allowed more expansion of the covered defect than BioGlue (6.3 ± 3.9 vs. 1.4 ± 1.0 mm, p < 0.001).Conclusion The tested sealants demonstrated high sealing efficacy. While BioGlue was superior in resisting higher ventilation pressure, TachoSil possessed better elasticity.
Keywords: experimental; lung; air leak; sealant